2018
DOI: 10.1080/15476286.2018.1556084
|View full text |Cite
|
Sign up to set email alerts
|

Length and secondary structure of the 5′ non-coding regions of mouse p53 mRNA transcripts - mouse as a model organism for p53 gene expression studies

Abstract: Transcription initiation sites of Trp53 gene in mice were determined using the 5′RACE method. Based on sequence alignment of the 5′-terminal regions of p53 mRNA in mammals, the site for the most abundant transcript turned out to be essentially identical with that determined for human TP53 gene and slightly differed for the longest transcripts, in mice and humans. Secondary structures of the 5′-terminal regions of the shorter, most abundant and the longest mouse transcripts were determined in vitro and the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…This is in line with earlier observations concerning the identification of mouse transcription promoter regions [37]. Interestingly, the comparison of the 5′-terminal sequences of mouse mRNA-122 and of human P1-initiated p53 mRNA revealed that the transcripts differ only by a single nucleotide in spite of a substantially different length of their 5′UTRs [36]. We also detected longer transcripts, termed as mRNA-247, which comprise the 5′UTR region of approximately 247 nucleotides in length.…”
Section: Transcription Initiation Sites and Secondary Structure Ofsupporting
confidence: 90%
See 4 more Smart Citations
“…This is in line with earlier observations concerning the identification of mouse transcription promoter regions [37]. Interestingly, the comparison of the 5′-terminal sequences of mouse mRNA-122 and of human P1-initiated p53 mRNA revealed that the transcripts differ only by a single nucleotide in spite of a substantially different length of their 5′UTRs [36]. We also detected longer transcripts, termed as mRNA-247, which comprise the 5′UTR region of approximately 247 nucleotides in length.…”
Section: Transcription Initiation Sites and Secondary Structure Ofsupporting
confidence: 90%
“…Recently, we determined transcription initiation sites for the mouse Trp53 gene by the 5′RACE method [36]. The most frequent transcripts isolated from the embryos, liver and thymus, termed as mRNA-122, contain the 5′UTR comprising approximately 122 nucleotides.…”
Section: Transcription Initiation Sites and Secondary Structure Ofmentioning
confidence: 99%
See 3 more Smart Citations